2002
DOI: 10.1088/0953-8984/14/22/314
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic spin Hamiltonian approaches for 3d8 and 3d2 ions in a trigonal crystal field - perturbation theory methods versus complete diagonalization methods

Abstract: In this paper, we critically review the existing microscopic spin Hamiltonian (MSH) approaches, namely the complete diagonalization method (CDM) and the perturbation theory method (PTM), for 3d8(3d2) ions in a trigonal (C3v, D3, D3d) symmetry crystal field (CF). A new CDM is presented and a CFA/MSH computer package based on our crystal-field analysis (CFA) package for 3dN ions is developed for numerical calculations. Our method takes into account the contribution to the SH parameters (D, g∥ and g⊥) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…where B and C are the Racah parameters, B kl are the CF parameters in the Wybourne notation [25,26] (the relationships between the Wybourne notation and Ballhausen's conventional notation in Ref. [17] for CF parameters are given in Ref.…”
Section: Calculationmentioning
confidence: 99%
“…where B and C are the Racah parameters, B kl are the CF parameters in the Wybourne notation [25,26] (the relationships between the Wybourne notation and Ballhausen's conventional notation in Ref. [17] for CF parameters are given in Ref.…”
Section: Calculationmentioning
confidence: 99%
“…(3d 8 ) ions in some crystals [13,[18][19][20]. They found that, for 3d 2 and 3d 8 ions at trigonal symmetry sites, although the SO mechanism is the most important one, the SS and SOO interactions were found important.…”
Section: +mentioning
confidence: 99%
“…where B kq are the CF parameters and B 43 = −B [14,29], taking into account the ZFS and Zeeman terms [14,15,29], can be written as [17] …”
Section: Theorymentioning
confidence: 99%
“…The MSH theory enables to correlate optical spectroscopy and structural data with the spin-Hamiltonian (SH) parameters extracted from the EPR spectra. Hence, the MSH studies of transition metal ions in crystals can provide a great deal of microscopic insight concerning the crystal structure, structural disorder, phase transitions and pressure behaviour as well as the observed magnetic and spectroscopic properties [17]. To study these properties, using the perturbation method (PTM), Pereosyan and Mirzakhanyan [18], Shang et al [19], and Huang [20] obtained a high-order perturbation formula for the SH parameters of d 8 ions at trigonal symmetry, including spin-orbit (SO) interaction only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation